IFRS for SMEs: Eine Alternative für den Einzelabschluss aus Sicht des deutschen Mittelstandes? - Klaus Henselmann; Martin Klein; Maren Wiese (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Rechnungswesen und Prüfungswesen, 2010)
– The objective of the IFRS for SMEs is to provide SMEs an attractive accounting alternative according to international standards. The paper analyses the differences compared to the German-GAAP and highlights the consequences for medium-sized entities in Germany.
Keywords: G18; G38; K22; M41; M42; 650; Accounting; full IFRS; IFRS; IFRS for SMEs; non-listed companies; small and medium-sized entities (SMEs)